2022
DOI: 10.1097/ju.0000000000002491
|View full text |Cite
|
Sign up to set email alerts
|

A Nationwide Analysis of Risk of Prostate Cancer Diagnosis and Mortality following an Initial Negative Transrectal Ultrasound Biopsy with Long-Term Followup

Abstract: Purpose: Magnetic resonance imaging (MRI) targeted prostate biopsy has been shown to find many high-grade prostate cancers in men with concurrent negative transrectal ultrasound (TRUS) systematic biopsy. The oncologic risk of such tumors can be explored by looking at long-term outcomes of men with negative TRUS biopsy followed without MRI. The aim was to analyze the mortality after initial and second negative TRUS biopsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 22 publications
0
20
0
Order By: Relevance
“…However, doubt has been cast on whether these cancers are oncologically aggressive. We and other groups have shown that the long‐term risk of prostate cancer death in men with benign systematic biopsies is very low 18,21 ; if MRI targeting identifies many histologically defined Gleason score ≥ 7 tumors in a group of men with low prostate cancer mortality, it is clear that most of the tumors are in fact indolent despite their histology 10 . This suggests that current guidelines on how to histologically evaluate and grade MRI‐targeted biopsies may need revision.…”
Section: Discussionmentioning
confidence: 99%
“…However, doubt has been cast on whether these cancers are oncologically aggressive. We and other groups have shown that the long‐term risk of prostate cancer death in men with benign systematic biopsies is very low 18,21 ; if MRI targeting identifies many histologically defined Gleason score ≥ 7 tumors in a group of men with low prostate cancer mortality, it is clear that most of the tumors are in fact indolent despite their histology 10 . This suggests that current guidelines on how to histologically evaluate and grade MRI‐targeted biopsies may need revision.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, although some metachronous tumors maintain molecular subtype membership of initial tumors, 12.5% of metachronous tumors had unmatched subtypes. 1 Considering existing evidence from published studies about the clonal relatedness between UTUC and BUC, 8e10 genomics combined with transcriptomics might still be required to identify a more complete molecular subtype of metachronous and synchronous urothelial carcinomas.…”
mentioning
confidence: 99%
“…To the Editor: We were interested to read the impressive study by Petros et al 1 and would like to congratulate the authors for their excellent findings. The authors used whole transcriptome RNA sequencing to systematically analyze same-patient samples of upper tract urothelial carcinoma (UTUC) and bladder urothelial carcinoma (BUC) and divided them into 4 groups: UTUC-metachronous BUC, BUC-metachronous UTUC, synchronous UTUC-BUC and UTUC without BUC (UTUC-only).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To the Editor: We read with great interest the work of Kawa et al on prostate cancer diagnosis and survival following a negative transrectal ultrasound-guided biopsy in a large cohort from Denmark. 1 We have previously published in The Journal of Urology ® on survival following negative prostate biopsy using data from the screening arm of the Prostate, Lung, Colorectal, and Ovarian cancer trial, and found a prostate cancer-specific mortality rate of 1.1% at a median followup of 12.9 years. 2 These figures were recently updated, using similar methodology by Pierre-Victor et al, to 1.2% at 16.6 years.…”
mentioning
confidence: 99%